Lateral lymph node and its association with distant recurrence in rectal cancer: A clue of systemic disease. (December 2020) - Kim, Young Il; Jang, Jong Keon; Park, In Ja; Park, Seong Ho; Kim, Jong Beom; Park, Jin-Hong; Kim, Tae Won; Ro, Jun-Soo; Lim, Seok-Byung; Yu, Chang Sik; Kim, Jin Cheon
Abstract: We analyzed oncologic outcomes according to pre-/post-LPLN enlargement. Rectal cancer patients who underwent resection post-PCRT during 2008–2012 were enrolled. Magnetic resonance imaging pre-/post-PCRT were re-evaluated. LNs with short axis (SA) ≥7 mm pre-PCRT and ≥4 mm post-PCRT were defined as enlarged nodes. Of 798 patients enrolled, recurrence occurred in 55 (6.9%) local, 17 (2.1%) lateral, and 179 (22.4%) distal regions. Patients with LPLN SA ≥7 mm pre-PCRT showed worse local recurrence-free survival (RFS), lateral RFS, and distant RFS ( p < 0.001, 0.002, and 0.005, respectively). LN shrinkage post-PCRT to SA<4 mm showed better 5-year local RFS (83.5% vs. 78.3%, p = 0.045), but distant RFS was similar irrespective of LN shrinkage to <4 mm. Among patients with pre-PCRT SA ≥7 mm, node shrinkage to SA<4 mm after PCRT presented with lower incidence of local recurrence but did not benefit in distant recurrence. Lateral node sampling did not improve local recurrence control, resulting in a 5-year local RFS of 75.4% in patients undergoing lateral node sampling and 83.2% in those not undergoing lateral node sampling ( p = 0.722). Four (66.7%) patients had lateral recurrence in the same area of the enlarged nodes identified pre-PCRT. For patients assessed with pre-PCRT nodes ≥7 mm, response to PCRT did not guarantee better outcomes. Highlights: Lateral pelvic lymph node larger than 7 mm before PCRT presents higher recurrence risk in local, lateral, and distant areas. Patients with enlarged lateral lymph nodes before PCRT are prone to distant metastasis regardless of treatment response. Lateral node sampling did not improve local recurrence control, thus seems insufficient.